Sosialisasi Berita Palsu di Media Sosial Kepada Masyarakat di Desa Sidodadi Kecamatan Kota Kisaran Barat - Ardiansyah Sinaga; Husni Thamrin (Yayasan Literasi Sains Indonesia, 2023)
In this era of globalization, the development of technology and information and communication is growing very rapidly and also provides many benefits. This indicates that globalization in Indonesian society has become a part of life. The development of information and communication technology also affects all aspects of life, this is felt by the increasing emergence of increasingly sophisticated information and communication equipment. One of the bad effects of the acceleration of globalization is hoax news. The government continues to socialize how to respond to hoax news that appears on social media. Through this Field Work Practice activity, the practitioner provides assistance by educating about hoax news on social media and how to match the truth and its sources to the community in Sidodadi Village, West Kisaran City District. The process of providing this assistance was also carried out in the Field Work Practice II mini project, using the groupwork method through the general or general intervention stage consisting of Assessment, Program Planning, Intervention, Program Evaluation, Monitoring and Termination.